Experimental investigation on performance, emission and combustion characteristics of neem oil bio diesel using ethanol blend. (2023) - Mohankumar, D.; Indharajith, P.; Sabarishankar, P.; Sanjaykumar, V.T.; Vignesh kumar, N.; Udhayakumar, N.
Abstract: Due to the rising mechanical requirements, the cost of customary powers is becoming more expensive. Rough oil use contributes to increasing environmental pollution, hence it is necessary to look into alternative fuel sources with little to no environmental impact before using them for vehicles and other purposes. The alternative fuel that is inferred and treated synthetically to suit the applications is bio-diesel blended with natural extracts. Neem oil was selected as the optional fuel mix for the current investigation because it is easily accessible. The electronic 4-stroke single chamber water cooled DICI (Direct Injection Compression Ignition) diesel motor for diesel is tested in the initial stage, and pattern data is gathered. Additionally, in the second step, trial investigations are done on similar motors with the same operating parameters using neem oil and ethanol mixed diesel with the proportions 7:2:1, 6.5:2:1.5, and 6:2:2. The results illustrate the limits of presentation and discharges of the various combinations. The alternative fuel mixture, which performed better in terms of motor execution and outflow management, was picked as the best mixture. Finally, the exhibition and outflow limits obtained from the aforementioned test are compared to the gauge data previously obtained using diesel. The results of the blends will be tested further in conventional automobiles.